Prevalence of specific learning disabilities among Gujarati medium primary school children - Shah, Chintan G; Buch, Pankaj M (Indian Journal of Child Health, 2019)
Introduction: Learning disability in children is an assorted group of disorders where the individual unpredictably fails to proficiently attain, regain, and use information. Objective: The objective of this study was to measure the prevalence of specific learning disabilities (SpLDs) such as dyslexia and dysgraphia among the Gujarati medium primary schoolchildren. Methods: A cross-sectional study was conducted in public schools of Gujarati medium among children aged 7–12 years from the second, third, and fourth standard. After obtaining a sociodemographic profile, a multilevel screening approach that begins with the identification of educational backwardness followed by exclusion of vision, hearing impairment, chronic health conditions, and subnormal intelligence was carried out among these children. In the last stage, remaining children were subjected to the National Institute of Mental Health and Neurosciences test for SpLDs. Results: The prevalence of SpLDs was 9.6% in sampled children, whereas 7.4%, 8.6%, and 7.1% had dyslexia, dysgraphia, and dyscalculia, respectively. Among children diagnosed with SpLD, 65.7% (n=25/38) of children had a combination of all three types of SpLDs. Conclusions: This study suggests that the prevalence of SpLDs in public schools is the same as private schools and metro center. We have used a multilevel screening approach that can be utilized for early identification of children with SpLD by Rashtriya Bal Swasthya Karyakram team without imposing load on specialist services. There is a need for sensitization of school teacher for timely referral, remediation strategies, and policy interventions to improve school performance and to reduce dropouts of schoolchildren.